Cyberculture and the subaltern : weavings of the virtual and real - Gajjala, Radhika, 1960- (Lexington Books, 2013)
"Through inter-disciplinary lenses enabled by cultural studies and feminist methodologies, Cyberculture and the Subaltern: Weavings of the Virtual and Real, edited by Radhika Gajjala, looks at online microfinance, new technologies, virtual world marketing, and handloom contexts from India and Africa in relation to development discourse that posits a binary between "tradition" and modernity. Through actual (auto)ethnographic engagement in these contexts, the contributors to this volume reveal the interdependence of the economic, political, cultural, and social in the production of the subaltern online"--